KEBIJAKSANAAN PENGEMBANGAN SUMBER DAYA MANUSIA MENGHADAPI ERA TINGGAL LANDAS - Sofian Effendi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1991)
Human resources are a very important factor in their role to the development of many developing countries such as Indonesia. The development of human resources should be carefully planned by paying attention to the needs of its social structure as well as its national technology. For this reason, it needs appropriate relied strategy to be able the industrial community to prepare it self thoroughly during the present take-off stage era. One of its strategy is by identifying the problems which would possibly take place around the take-off stage, both domestic as well as foreign. The shift of the world economic structure that happened as a consequence of the development of new technology, and the slackening of the cold war between two very powerful countries are two most essential questions among the foreign problems; whereas the obstacles that come from the country itself are among others the extremely low labour productivity of Indonesia as a consequence of the poor educational level of the majority of the population, the low wages, the serious problems of unemployment,the inappropriate work ethics and work disciplines, and its inability inworld competition.Eased on the above statements, the most important effort to obtain potential human resources during the coming take-off stage era is by improving the quantity and quality of resources to be able to answer every challenge that may emerge later, and by putting high priority on the overall reorganization of human resources of Indonesiato become one of much stronger integrity.